EVALUATION AND DESIGN OF PEDESTRIAN FACILITIES CASE STUDY: ITB GANESHA CAMPUS - Erganikasalist Kautsar, Cyndara
Pedestrian facilities are crucial for supporting and implementing the development of sustainable transportation systems. By applying the concept of walkability, pedestrians can walk comfortably, safely, and conveniently. Pedestrian facilities are also influenced by the perceptions of pedestrians when walking on these paths. Therefore, an assessment of the conditions and facilities of the pedestrian paths is necessary to create a pedestrian-friendly area. This study discusses the evaluation of pedestrian facilities in an educational area, namely the ITB Ganesha Campus, where pedestrian paths are the primary routes used. Based on the evaluation results, recommendations will be provided in the form of pedestrian facility designs that refer to the Regulation of the Minister of Public Works and Housing (Permen PUPR) No. 7 of 2023 and the Master Plan of ITB Ganesha Campus. The evaluation of pedestrian facilities is carried out using two methods: the Walkability Index (WI) evaluation to assess the conditions and facilities of the pedestrian paths, and the Walking Effort evaluation method through the Equivalent Walking Distance equation to assess the effort required by pedestrians to reach their destination. The WI assessment uses indicators found in Permen PUPR No. 5 of 2023. Meanwhile, the assessment indicators for pedestrian effort include travel distance, conflict points, number of steps, walking time, and waiting time. The analysis results for the WI score calculation show scores above 65, which fall into the "Fairly Good" category for each observation route. Meanwhile, the analysis of the effort expended shows more than a 20% increase in the average distance from the actual distance. This effort assessment is also analyzed using pedestrian perceptions of the walking route distance, and the results indicate that the walking distance is still acceptable. The recommendations provided for each observation route are dominated by infrastructure parameters for pedestrians with special needs, additional supporting facilities such as continuous shading, information providers, and lighting, as well as the conditions and quality of the pedestrian paths. These recommendations can be aligned with the suggestions given in the ITB Ganesha Campus Master Plan, resulting in a final design recommendation for improving pedestrian facilities at the ITB Ganesha Campus.